Antifungal and antioxidant effects of phenolic acids and flavonol glycosides from Tetraclinis articulata. (3rd February 2022) - Rguez, Safa; Papetti, Adele; Bourguou, Soumaya; Msaada, Kamel; Hammami, Majdi; Mkadmini Hammi, Khaoula; Hamrouni Sellami, Ibtissem
Abstract: The present study investigated the crossing of extraction solvent with vegetative stage of Tetraclinis articulata to result in an extract having a strong antifungal and antioxidant activities. Results showed that dichloromethane extract at vegetative stage were the most active to inhibit Botrytis cinerea mycelial growth and conidia germination. The identification by HPLC-MSn of active extract revealed that phenolic acids (sandaracopimaric, communic, and cupressic acids) were responsible for antifungal activity. However, methanol and fructification stage were the best solvent and phonological stage to extract bioactive compounds with antioxidant activity. This methanolic extract from fructification stage was also characterized by the highest contents of polyphenols and flavonoids. According to HPLC-MSn, flavonol glycosides (myricetin 3- O -rhamnoside, quercetin-7- O -rhamnoside, quercetin-7- O -rutinoside, and trimeric form of kaempferol) were responsible for antioxidant activity of T. articulata . Consequently, T. articulata extracts could be used as an alternative to chemical pesticides for the treatment of grey mould disease and oxidative stress.